The NDVI and spectral decomposition for semi-arid vegetation abundance estimation (International Journal of Remote Sensing, 1998)
This paper describes the use of the Normalized Difference Vegetation Index (NDVI) and spectral decomposition techniques to estimate vegetation abundance using ground-based spectroradiometric data of semi-arid vegetation. It is found that the NDVI provides a better measure of the proportion of directly irradiated leaves within the field-of-view of the spectroradiometer than it does the Leaf Area Index or biomass. Moreover, it is found that spectral decomposition isolates a factor which is strongly influenced by spectral variation at the region of the red edge. This factor is highly correlated with the NDVI -(R2=0.91) and as such also provides a good estimate of the proportion of directly irradiated leaves. It is suggested that spectral decomposition techniques provide a unique framework in which to analyse the factors affecting the spectral response of vegetation.
doi: 10.1080/014311698214217